LEADERSHIP STYLES IN ORGANIZATIONS PARTICIPATING IN THE UN GLOBAL COMPACT - Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2015)
Purpose - The United Nations Global Compact is a voluntary initiative in four areas as human rights, labor, environment, and anticorruption with 10 universal principles. This network brings corporations, nongovernmental organizations, employees, and people together. There is a need to have responsible and committed leaders to promote good corporate citizenship in the framework of Global Compact. Leaders have a unique position through which they can influence factors concerning organizations' and employees' behavior. According to the areas of UN Global Compact, some leadership styles seem to better suit to benefit economies, societies, markets, and people all over the world than the others. By this way, from the theoretical perspectives, the primary purpose of this chapter is to investigate the leader's behavior and different leadership styles in organizations that are the part of Global Compact platform. There are certain leadership theories - transactional, transformational, sustainable, ethical, and servant - which are examined in Global Compact initiatives. Design/methodology/approach - An extensive literature research is conducted in order to understand the different types of leadership styles while organizations are adapting and understanding the Global Compact principles. Findings - Modern leadership styles especially ethical leadership behavior should be effective to comply with universal principles and organizations can also have commitment to disclose a report with powerful leadership. Research limitations/implications - However, this research is a theoretical study; for further studies, longitudinal studies can be conducted to understand the leadership styles from the perspective of Global Compact principles, and these different managers' behaviors can be measured. Practical implications - This study may be useful for the board of directors and managers since they should participate and adapt themselves to this initiative about how they should behave in the right way. Originality/value - There is a lack of behavioral studies while analyzing Global Compact principles. Especially examining leadership theories that are complied with these principles will add a value to the literature in this area.
Keywords: Leadership styles; Global Compact initiative; CORPORATE SOCIAL-RESPONSIBILITY; ETHICAL LEADERSHIP; SERVANT LEADERSHIP; TRANSACTIONAL LEADERSHIP; TRANSFORMATIONAL LEADERSHIP; SUSTAINABILITY; BEHAVIOR; CSR; CEO; PERFORMANCE; Environmental Sciences & Ecology; International Relations; Business & Economics